Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

New insights towards strikingly improved room temperature ethanol sensing properties of p-type Ce-doped SnO2 sensors - Kumar, Manjeet; Bhatt, Vishwa; Abhyankar, A. C.; Kim, Joondong; Kumar, Akshay; Patil, Sagar H.; Yun, Ju-Hyung (Scientific Reports, 2018)
In this article, room temperature ethanol sensing behavior of p-type Ce doped SnO2 nanostructures are investigated successfully. Interestingly, it is examined that the abnormal n to p-type transition behavior is caused by Ce doping in SnO2 lattice. In p-type Ce doped SnO2, Ce ion substituting the Sn is in favor of generating excess holes as oxygen vacancies, which is associated with the improved sensing performance. Although, p-type SnO2 is one of the important materials for practical applications, it is less studied as compared to n-type SnO2. Pure and Ce doped SnO2 nanostructures were successfully synthesized by chemical co-precipitation method. The structure, surface morphology, unpaired electrons (such as free radicals), and chemical composition of obtained nanoparticleswere studied by various kinds of characterization techniques. The 9% Ce doped SnO2 sensors exhibit maximum sensor response of similar to 382 for 400 ppm of ethanol exposure with fast response time of similar to 5 to 25 sec respectively. Moreover, it is quite interesting that such enhancement of ethanol sensing is unveiled at room temperature, which plays a key role in the quest for better ethanol sensors. These remarkably improved sensing results are attributed to uniformly distributed nanoparticles, lattice strain, complex defect chemistry and presence of large number of unpaired electrons on the surface.